Ecological and aesthetic aspects of the organization of public use areas by means of green infrastructure - Maksymenko , N. V.; Gololobova О. О. (Man and Environment. Issues of Neoecology, 2023)
Relevance. Trends in the development of the concept of green infrastructure in post-Soviet cities prompts a rethinking of approaches to landscaping the areas surrounding administrative buildings, educational and research institutions. The Northern Building of Karazin University is one of the symbols of education in Kharkiv, and the ecological reconstruction of the space in front of the building is also relevant. Objective. To develop a concept and formulate design proposals for the improvement of the territory in front of the main facade of the North Building of Karazin University. Methods. To develop the concept, we analyzed historical and cartographic information. To create the project, we used the program Realtime Landscaping Architect 2023.02, Trial Free Version. Results. Based on the analysis of the history of the formation of the territory on Svobody Square between the buildings of Karazin University and taking into account its current state, it is proposed to develop a landscape idea of using new environmental trends in urban greening, which was launched during the Greening of the Planet campaign (2021). A proposal for the ecological reconstruction of the area in front of the main facade of the North Building of Karazin University at 6 Svobody Square is substantiated. Kharkiv, using cultivars of the grafted form of fine-sawed sakura on a tall stem to create new landscaping locations. The assortment catalog of plant material proposed for the renovation of the parterres in front of the building was compiled and the approximate economic costs for its implementation were calculated. The use of small architectural forms, such as benches for rest, authentic fences, etc. is substantiated. An animation file of the project in .mp4 format was created for visualization. Conclusions. The developed proposal for the ecological reconstruction of the area in front of the main facade of the Northern Building of Karazin University will ensure the creation of a single style solution for the landscaping of the territory of Freedom Square and the buildings located on it.